Comparison of outcome of open reduction and internal fixation versus closed treatment in pediatric mandible fractures-a retrospective study. Issue 3 (March 2021) - Bansal, Adity; Yadav, Poonam; Bhutia, Ongkila; Roychoudhury, Ajoy; Bhalla, Ashu Seith
Abstract: The aim of the study was to compare the outcome and complications of open reduction and internal fixation (ORIF) with closed treatment, as well as to review the literature. This was a retrospective study on pediatric patients with mandible fracture. The primary objective was a comparison of outcomes in terms of bone healing, maximal incisal opening (MIO), and occlusion, and the secondary objective was to review complications. A total of 77 pediatric patients (age <12 years) were managed with closed treatment and 23 with ORIF. In all, 62 patients were found with a single fracture (22 patients with parasymphysis fracture and 21 with condyle fracture, followed by symphysis, angle, and body fracture) and 38 patients with more than one fracture, with symphysis and bilateral condyle fracture being the most common. Bone healing was observed in all the patients. Mean MIO was 26.9 ± 2.8 mm and 29.3 ± 1.7 mm in the closed and ORIF group, respectively, and the difference was statistically nonsignificant (p = 0.5). One patient (1.3%) had deranged occlusion, and mobility was observed in one patient (1.3%) in the closed treatment group. Infection and nerve paresthesia were not seen in any patient at follow-up. Although closed treatment is preferred, as it preserves the soft tissue and periosteum, a displaced mandible fracture especially with co-existing condylar fracture should be treated by ORIF.